Sociodemographic, health and lifestyle habits profile of long age elderly in a municipality in the interior of Bahia (Research, Society and Development, 2021)
Objetive: Characterize the sociodemographic, health and lifestyle habits of long-lived elderly in a municipality in the interior of Bahia. Methodology: This is a cross-sectional, descriptive, population-based study carried out with elderly people between 80 and 107 years old, after accepting to participate in the research, the elderly were for submeted cognitive testing and those with preserved cognitive status answered a questionnaire prepared by researchers on the sociodemographic profile, health conditions and life habits. Results: The final sample of this study was composed of 87 long-lived elderly, the majority female 52.9%, without schooling 71.3%, with family income between US$194.0 and US$582.0 73.6%, with systemic arterial hypertension 46%. As for lifestyle habits, the oldest olds surveyed reported not using tobacco 87.4% and alcoholic beverages 85.1%, having an adequate nutritional status 37.9%, not practicing physical activity 60.9%, living in environments non-stressful 83.9%, sleep ≥8 hours of sleep 92%. Conclusion: These findings may contribute to a better understanding of the profile of long-lived residents of small cities with low HDI so that actions aimed at promoting health and healthy living habits are strengthened and implemented taking this audience into account.